Environmental Crimes in The Perspective of Criminal Law and Ecosystem Protection in Indonesia - Rudolf Silaban (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Law Number 32 of 2009 concerning Environmental Protection and Management is the legal basis that regulates various forms of environmental violations, ranging from pollution to destruction of natural resources. The aim is to analyze how criminal law is applied to deal with environmental crimes in Indonesia and create existing conditions and enforcement laws. The research method commonly used in studying environmental crimes in Indonesia is a qualitative approach, which involves interviews with key stakeholders such as government officials, environmental activists, and local communities. The results of this study show that environmental protection is very important and should be a priority for all parties. So that the criminal law that regulates environmental crimes can encourage the awareness and responsibility of the same person and the same person in preserving the environment. The implementation of strict criminal law against environmental crimes is expected to have a deterrent effect on perpetrators who damage the environment.